2017
DOI: 10.1177/1938965517730314
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Response to Authentic-Language Versus English-Language Menu Labeling in Ethnic Dining

Abstract: Many ethnic restaurants use authentic-language labels (e.g., “Khao Pad Sapparod”), as opposed to English-language labels (e.g., “Pineapple Fried Rice”), in the menu to make their dishes appeal more authentic. Yet, the effectiveness of authentic-language labels is not well understood. To address this gap, the present research examines consumers’ attitudes toward a menu as a function of (a) authentic-language versus English-language menu labeling and (b) the consumer’s Need for Cognitive Closure (NFCC)—a fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Obviously, by developing clearer language (in this case Indonesian) for product information statements (Manca et al, 2019). Therefore, this study result is also similar to previous research which states that consumers will tend to prefer label language that is easy to understand (Choi et al, 2018). As previous research has shown that a lack of ability to understand language will only add to the great difficulty of information processing (Harzing & Feely, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…Obviously, by developing clearer language (in this case Indonesian) for product information statements (Manca et al, 2019). Therefore, this study result is also similar to previous research which states that consumers will tend to prefer label language that is easy to understand (Choi et al, 2018). As previous research has shown that a lack of ability to understand language will only add to the great difficulty of information processing (Harzing & Feely, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…Prior research posits that consumers' favorable attitudes toward the menu can influence their overall dining experiences (Choi et al, 2018). The findings of this study can further restaurant managers' understanding of how to leverage promotional cues on a menu to enhance solo diners' experiences.…”
Section: Practical Implicationsmentioning
confidence: 71%
“…A total of 277 U.S. adult consumers, recruited via Amazon’s Mechanical Turk (MTurk), participated in the study. MTurk has been shown to be a valid and reliable data collection platform that provides high-quality data for consumer experiments (Buhrmester et al, 2011; Paolacci et al, 2010) and is commonly utilized by hospitality researchers (Choi et al, 2018; Hanks et al, 2017; Zhang & Yang, 2019). We took several measures to ensure data quality.…”
Section: Methodsmentioning
confidence: 99%